Psychiatric rehabilitation and cognitive deficit for treatment-resistant depression - Cheng, Chih-Ming; Jeng, Jia-Shyun (Progress in brain research, 2023)
Patients with TRD often experience persistent impairment of affective, psychosocial, and cognitive function, which impedes their recovery. The continuation of pharmacotherapy for patients with TRD remains the cornerstone of functional recovery. Cognitive dysfunction is prevalent in patients with MDD and may make patients' depressive symptoms and psychosocial functioning worse, even in the remitted stage of illness. Deficits can manifest not only in specific cognitive domains but also in global cognitive function, which may reflect underlying persistent pathophysiological changes. Compared with nontreatment-resistant patients with MDD, patients with TRD exhibit greater subjective and objective cognitive impairment, which possibly contributes to a greater adverse impact on daily functioning. Cognitive and psychosocial remission should be a goal in treating MDD. How to appropriately and individualized perform pharmacological intervention, psychotherapy, neuromodulation, cognitive remediation or other rehabilitation treatment programs is a critical step to achieve our goal. Integrating multiple interventions that engage multiple physiological systems with a multidisciplinary team warrants increased attention, and personalized therapeutic programs may facilitate the complete restoration of patients' everyday functioning.